(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Homonymy is one of the widely observed linguistic phenomena in the Uzbek language and emerges in the process of language development. Homonyms, which are identical in form but different in meaning, demonstrate the multifaceted nature of the language. One of the key principles in identifying homonyms is context, as it plays a crucial role in determining the specific meaning in which a homonymous word is used. Therefore, the implementation of context-based translation algorithms is of great importance. This article focuses on the role of context in the translation of Uzbek homonyms by machine translation systems such as Google Translate, Yandex Translate, ChatGPT, and Tilmoch, and provides an analysis of the errors observed in these systems.